Pharmacogenetics of lithium response in bipolar disorder. (October 2010) - McCarthy, Michael J; Leckband, Susan G; Kelsoe, John R
Bipolar disorder (BD) is a serious mental illness with well-established, but poorly characterized genetic risk. Lithium is among the best proven mood stabilizer therapies for BD, but treatment responses vary considerably. Based upon these and other findings, it has been suggested that lithium-responsive BD may be a genetically distinct phenotype within the mood disorder spectrum. This assertion has practical implications both for the treatment of BD and for understanding the neurobiological basis of the illness: genetic variation within lithium-sensitive signaling pathways may confer preferential treatment response, and the involved genes may underlie BD in some individuals. Presently, the mechanism of lithium is reviewed with an emphasis on gene-expression changes in response to lithium. Within this context, findings from genetic-association studies designed to identify lithium response genes in BD patients are evaluated. Finally, a framework is proposed by which future pharmacogenetic studies can incorporate advances in genetics, molecular biology and bioinformatics in a pathway-based approach to predicting lithium treatment response.